METHODS AND PRINCIPLES OF TEACHING FOREIGN LANGUAGE (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
This article examines the key methods and pedagogical principles used in teaching the foreign language. As a minority language with unique phonological, grammatical, and cultural characteristics, foreign requires an integrated instructional approach. The study highlights communicative methods, structural techniques, and technology-enhanced learning, while emphasizing fundamental principles such as learner-centered instruction, cultural relevance, and gradual progression.